A Plastic Network Approach to Model Calving Glacier Advance and Retreat - Ultee, Lizz; Bassis, Jeremy N. (Frontiers in Earth Science, 2017)
Calving glaciers contribute substantially to sea level rise, but they are challenging to represent in models. Fine resolution is required for continental-scale models to accurately resolve calving dynamics, and in many cases glacier geometry is too complicated to be adequately reflected by more simplified models. Flowline models are able to resolve flow along the main branch of a glacier, but many of those in current use either ignore tributaries entirely or parameterize their effect using a measure of “equivalent width.” Here we present a simple method to simulate terminus advance and retreat for an interacting network of glacier branches, based on a model extending Nye's (1953) perfect plastic flow approximation to calving glaciers. We apply the method to case studies of four marine-terminating glaciers: Jakobshavn Isbræ and Helheim Glacier of Greenland, and Columbia and Hubbard Glaciers of Alaska. Given bed topography and upstream elevation history, our method reproduces observed patterns of terminus advance and retreat in all cases, as well as centerline profiles for all branches.